Rapid-Onset Opioids for Management of Breakthrough Cancer Pain: Considerations for Daily Practice - Bossi, Paolo; Escobar, Yolanda; Pea, Federico (Frontiers in Pain Research, 2022)
Background and Objective Rapid-onset opioids (ROOs) are effective treatments for breakthrough cancer pain (BTcP) given their rapid onset of action and relatively short duration of analgesia. The aim of this article is to describe specific considerations for the use of ROOs in daily practice, focusing on dose titration and treatment of specific populations. Type of Review We conducted a narrative review on the use of ROOs for BTcP. We selected papers according to the following search terms: “breakthrough cancer pain” and “rapid onset opioids”. Results ROOs may be considered as the most suitable drugs to treat BTcP and can be used “on-demand”. Several fentanyl formulations are available and have been associated with control of BTcP and with improvement in quality of life. Various titration schemes have been used to optimize ROO dosing; however, a dose-proportional scheme could be considered safe and effective in most patients. Specific formulations may be more suitable for specific patient subgroups; for example, patients with oral mucositis may prefer intranasal to oral formulations. Moreover, elderly patients or those without caregivers should be clearly educated on the use of these formulations. A key element in achieving successful treatment of BTcP is awareness of the barriers to pain management, including poor overall assessment, patient reluctance to take opioids or report pain, and physician reluctance to prescribe opioids. Conclusion A personalized approach is fundamental when prescribing a medication for BTcP, and careful attention should be given to drug choice and route of administration, and to the need for alternative therapeutic options.